MoveSchedule - Zouein, Pierette (1995)
Site layout planning is crucial for enhancing the overall efficiency of construction operations and for reducing materials (re)location costs. More importantly, it helps identify construction time periods with potential spatial conflicts due to limited space so that they can be avoided in early project plans. This research develops an integrated scheduler and space planner, MoveSchedule, that adjusts an initial project schedule to comply with site space limitations in the process of accommodating resource space needs as they change over time. MoveSchedule solves a constrained dynamic layout problem with the objective of minimizing resource transportation and relocation costs. Two-dimensional geometric constraints between relative positions of resources are being considered. Four different space profiles describe variations in resource space needs over time. The timing of these needs is inferred from the activity schedule. The layout construction algorithm that underlies MoveSchedule uses Constraint Satisfaction to find the set of all positions that meet the constraints on resources' positions and Linear Programming to find the optimal positions that minimize resource transportation and relocation costs. The solution is a sequence of layouts that describe changes in resource positions at discrete points in time corresponding to arrival and departure times of resources to and from site. When no solution is found, i.e., when the resources needed in a given time period cannot be accommodated on site without violating constraints on their positions, MoveSchedule adjusts durations or start dates of activities to lower the total space need over the problematic time period. MoveSchedule establishes a time-space relationship for each activity in the schedule based on alternative resource levels so that tradeoffs between activity duration and space need on site are possible. The resource levels describe different methods or crew-sizes for performing the activity. Two example applications of MoveSchedule illustrate other areas of application of the use of MoveSchedule for optimally solving a MINISUM location problem with constraints on acceptable locations of the new facility, and for evaluating and choosing between alternative material delivery schedules. MoveSchedule is validated using realistic project data and its solution is qualitatively assessed by an experienced engineer on that project.